Tổng hợp chất màu xanh (Co, Ni, Cu, Fe-Cordierit) sử dụng cho gạch ceramic - Tường, Phan Văn; Quý Sơn, Lê Đình (Vietnam Journal of Chemistry, 2014)
By using kaolin A Luoi (Thua Thien Hue province) and the necessary materials, the blue pigment with different shades in the cordierite lattice have been synthesized. The blue pigment will be enamelled with a transparent glaze on to ceramic tile and L*, a*, b*colour parameters of representative samples were measured with a colorimeter